On the Free Rider Problem in the M.D.P. Procedure - Henry, Claude (Review of Economic Studies, 1979)
Journal Article On the Free Rider Problem in the M.D.P. Procedure Get access Claude Henry Claude Henry Laboratoire d'Econométrie de l'Ecole Polytechnique, Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 2, April 1979, Pages 293–303, https://doi.org/10.2307/2297052 Published: 01 April 1979 Article history Received: 01 May 1977 Accepted: 01 December 1977 Published: 01 April 1979